Numerical forecast of groundwater inflow to the mines of the Legnica-Głogów Copper District with a particular emphasis on the “Polkowice-Sieroszowice” mine - Gurwin, Jacek; Wcisło, Marek (Geology, Geophysics and Environment, 2024)
The paper presents the results of work on the numerical hydrogeological model of the mines of theLegnica-Głogów Copper District (LGCD) in  Poland. Due to the extensive impact on the rock mass and the multi-layer depression cone caused by drainage, the model covers an area of 3,049 km2 . The complicated, mutual hydraulic connections of the multi-aquifer hydrogeological system required the model to cover the area beyond the range of mining areas, and to separate 17 numerical layers. The research was carried out in the GMS software environment using Modflow computing modules. The model was updated successively, since its structure, parameters, and boundary conditions are subject to change. It was also additionally calibrated based on new data from measurements in piezometers and changes recorded in inflows to the excavations. The simulations made it possible to determine the exact water balance, with a particular emphasis on the Sieroszowice mining area, where sudden unexpected inflows were noted. Subsequently, two prognostic simulations were performed to estimate dynamic water inflows to mine workings in the years 2020 and 2025.